El Pinciano y san Basilio, a propósito de la versión de Bruni de la Epistula ad adulescentes - Martínez Manzano, Teresa (Exemplaria Classica, 2010)
The Latin translation by Leonardo Bruni of Saint Basil´s Epistula ad adulescentes enjoyed a great diffusion in the 15th and 16th centuries as a grounding text of humanistic culture. On the occasion of the Greek-Latin edition of Saint Basil´s text by Pinciano in 1519, the Spanish scholar wrote also some critical remarks on Bruni´s translation. These remarks by Pinciano make up the subject-matter of this paper.